Enhancing coherent transport in a photonic network using controllable decoherence - Devon N. Biggerstaff; René Heilmann; Aidan A. Zecevik; Markus Gräfe; Matthew A. Broome; Alessandro Fedrizzi; Stefan Nolte; Alexander Szameit; Andrew G. White; Ivan Kassal (Nature Communications, 2016)
The efficiency of coherent transport can be enhanced through interaction between the system and a noisy environment. Here, Biggerstaff et al. report an experimental simulation of environment assisted coherent transport using laser-written waveguides, showing that controllable decoherence yields an increase in transport efficiency.